Plant Polysaccharides Modulate Biofilm Formation and Insecticidal Activities of Bacillus thuringiensis Strains - Li, Mengmeng; Shu, Changlong; Ke, Wang; Li, Xiaoxiao; Yu, Yiyan; Guan, Xiong; Huang, Tianpei (Frontiers in Microbiology, 2021)
After the biological pesticide Bacillus thuringiensis (Bt) is applied to the field, it has to remain on the surface of plants to have the insecticidal activity of insect pests. Bt can form biofilms on the surface of vegetable leaves, which were rich in polysaccharides. However, the relationship between polysaccharides of the leaves and the biofilm formation as well as the insecticidal activities of Bt is still unknown. Herein, this study focused on the effects of plant polysaccharides pectin and xylan on the biofilm formation and the insecticidal activities of Bt strains. By adding pectin, there were 88 Bt strains with strong biofilm formation, 69 strains with weak biofilm formation, and 13 strains without biofilm formation. When xylan was added, 13 Bt strains formed strong biofilms, 98 strains formed weak biofilms, and 59 strains did not form biofilms (Fig. 1). This indicated that two plant polysaccharides, especially pectin, modulate the biofilm formation of Bt strains. The ability of pectin to induce biofilm formation was not related to Bt serotypes. Pectin promoted the biofilms formed by Bt cells in logarithmic growth phase and lysis phase at the air-liquid interface, while it inhibited the biofilms formed by Bt cells in sporangial phase at the air-liquid interface. The dosage of pectin was positively correlated with the yield of biofilms formed by Bt cells in logarithmic growth phase or lysis phase at the solid-liquid interfaces. Pectin did not change the free-living growth and the cell motility of Bt strains. Pectin can improve the biocontrol activities of spore-ICPs mixture of Bt and BtK commercial insecticides as well as the biofilms formed by the logarithmic growth phase or lysis phase of Bt cells. Our findings confirmed that plant polysaccharides modulate biofilm formation and insecticidal activities of Bt strains, and built a foundation for the construction of biofilm-type Bt biopesticides.